Disharmony in the heart of Borneo: a closer look at forestry conflicts in the tropics - Yasmi, Yurdi (Cuvillier Verlag, 2003)
Conflict has always been part of human life. For that reason, conflict is often viewed as a normal and unavoidable feature, including in the forestry sector, regardless of the cultural, spatial and temporal setting. Due to this problem, it is imperative to understand the broader picture of forestry conflicts. This understanding is critical in order to help find ways and mechanisms to manage the occurence of conflicts in the forestry sector and to develop informed policy measures. This study looked closely at underlying causes of conflict between local people and other stakeholder groups in East Kalimantan Indonesia. Results show that conflicts were triggered by many factors not only limited to interest. Various levels or intensity of conflict were discussed. In contrast to the prevailing understanding in theory and practice, which sees conflicts over forest management mainly as the result of competing interests, this study concludes that interests do not necessarily play a major role as causes of conflicts. The behaviour of actors, as well as emotions and perceptions can play a much more important role.